2022
DOI: 10.3390/f13122104
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Identification of Larix sibirica Ledeb. Damage Caused by Erannis jacobsoni Djak. Based on UAV Multispectral Features and Machine Learning

Abstract: While unmanned aerial vehicle (UAV) remote sensing technology has been successfully used in crop vegetation pest monitoring, a new approach to forest pest monitoring that can be replicated still needs to be explored. The aim of this study was to develop a model for identifying the degree of damage to forest trees caused by Erannis jacobsoni Djak. (EJD). By calculating UAV multispectral vegetation indices (VIs) and texture features (TF), the features sensitive to the degree of tree damage were extracted using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…In this paper, traditional machine learning RF and deep learning CNN were utilised as algorithms for model construction. When using all the samples for modelling, CNN showed better results compared to RF, a finding which is consistent with our previous research and Kumar et al’s findings on using deep learning for diagnosing plant early blight and late blight [ 38 , 65 ]. In addition, we found that the size of the sample had an impact on the model construction process, so we tested its performance, and an optimal model was obtained by changing the sample size.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this paper, traditional machine learning RF and deep learning CNN were utilised as algorithms for model construction. When using all the samples for modelling, CNN showed better results compared to RF, a finding which is consistent with our previous research and Kumar et al’s findings on using deep learning for diagnosing plant early blight and late blight [ 38 , 65 ]. In addition, we found that the size of the sample had an impact on the model construction process, so we tested its performance, and an optimal model was obtained by changing the sample size.…”
Section: Discussionsupporting
confidence: 91%
“… where DR denotes the rate of leaf loss and takes values between 0 and 100%, and L h and L d denote the number of healthy and damaged needles, respectively. On this basis, through the experience of visual discrimination in field and the classification criteria in previous studies, the results were classified into pest damage levels based on Table 1 [ 38 ], where the final classification results of 210 larch trees into healthy, mild, moderate, and severe levels are shown.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al [17] selected 15 potential vegetation indices based on UAV multispectral images and used the minimal redundancy maximal relevance (MRMR) algorithm to select three sensitive spectral features for the construction of an areca yellow leaf disease classification model, ensuring the maximum relevance of the feature while removing the advantage of redundant features. Ma et al [18] used analysis of variance (ANOVA) and successive projection algorithm (SPA) to extract sensitive vegetation index features and texture features of forest trees with different damage levels to improve the generalization ability of the Erannis jacobsoni Djak severity model. In addition, the appropriate choice of data analysis method is very important, as it directly affects the reliability and accuracy of the results.…”
Section: Introductionmentioning
confidence: 99%